High areal capacity cathode and electrolyte reservoir render practical Li-S batteries. (August 2017) - Qin, Furong; Wang, Xiwen; Zhang, Kai; Fang, Jing; Li, Jie; Lai, Yanqing
Abstract: With the considerable development in sulfur cathode, Li-S batteries have recently witnessed a significant improvement, especially in the gravimetric capacity and cycling performance. However, maintaining high energy density of Li-S batteries and their commercialization relies on the high areal loading and high utilization of active material on the electrode, which are always ignored in the most fundamental research reports. For the Li-S batteries with much higher sulfur loading, except for the well-known issues about polysulfide dissolution, some new issues such as electron and ion transport in thick cathode, depletion of electrolyte and lithium dendrite growth need to be addressed. Here, a Li-S battery with a high areal capacity is proposed by a systematic strategy incorporating two approaches as follows: 1) a hierarchically porous carbon host containing graphene (G), mesoporous carbon (MPC) and super P (SP) diminishes polysulfide migration and guarantees fast electron and ion transport in thick cathode; 2) a glass-fiber (GF) membrane severs as the electrolyte reservoir to prevent the short circuit resulted from the deficiency of liquid electrolyte. With these methods, the Li-S batteries with an ultrahigh sulfur loading of 13 mg cm −2 provide a high areal capacity of 14.3 mA h cm −2 (1099 mA h g −1 ) at the first cycle and stable cycling performance with a reversible capacity of 628 mA h g −1 (8.16 mA h cm −2 ) after 75 cycles at 0.1 C. Graphical abstract: Highlights: SP, MPC and G are integrated into hierarchically porous G/MPC/SP for sulfur cathode with high sulfur loading. The sudden death of high-areal-capacity Li-S battery mainly originates from the accelerating Li dendrite growth. The GF interlayer can reserve electrolyte to maintain stable local current density, inhibiting Li dendrite growth.